A Study of Forced Convection in Non-Newtonian Hybrid Nanofluids Embedded in a Heated Cylinder Within a Hexagonal Enclosure by Finite Element Method - Md. Noor-A-Alam Siddiki; Saiful Islam; Mahtab U. Ahmmed; Md Farhad Hasan; Md. Mamun Molla (Mathematics)
Nanofluids have the proven capacity to significantly improve the thermal efficiency of a heat exchanging system due to the presence of conductive nanoparticles. The aim of this study is to simulate the forced convection on a non-Newtonian hybrid with a nanofluid (Al2O3-TiO2-H2O) in a hexagonal enclosure by the Galerkin finite element method (GFEM). The physical model is a hexagonal enclosure in two dimensions, containing a heated cylinder embedded at the center. The bottom, middle left, and right walls of the enclosure are all considered cold (<semantics>Tc</semantics>), while the top wall is considered to be moving, and the remaining middle, upper left, and right walls have the adiabatic condition. The Prandtl number (<semantics>Pr</semantics> = <semantics>6.2</semantics>), Reynolds number (<semantics>Re</semantics> = 50, 100, 300 and 500), power law index (n = <semantics>0.6</semantics>, <semantics>0.8</semantics>, <semantics>1.0</semantics>, <semantics>1.2</semantics> and <semantics>1.4</semantics>), volume fractions of nanoparticles (<semantics>ϕ</semantics> = <semantics>0.00</semantics>, <semantics>0.01</semantics>, <semantics>0.02</semantics>, <semantics>0.03</semantics> and <semantics>0.04</semantics>), and Hartmann numbers (<semantics>Ha</semantics> = 0, 10, 20 and 30) are considered in the model. The findings are explained in terms of sensitivity tests and statistical analysis for various <semantics>Re</semantics> numbers, n, and <semantics>Ha</semantics> numbers employing streamlines, isotherms, velocity profiles, and average Nusselt numbers. It is observed that the inclusion of <semantics>ϕ</semantics> improves the convective heat transfer at the surging values of <semantics>Re</semantics>. However, if the augmenting heat transfer requires any control mechanism, integrating a non-zero <semantics>Ha</semantics> number is found to stabilize the system for the purpose of thermal efficacy.